Geração Coca-Cola, Filhos da Revolução: Efeitos de sentido em canções da Legião Urbana - Santos, Cleverson Lucas dos (2016)
This study intend to comprehend the effects of meaning produced by the songs of Brasilia band Legião Urbana, under the French Discourse Analysis scope, considering the discursive production conditions in the constitution of young people and youth. Thus, it has like a started point a sample of the production of Legião Urbana band about three works of them during three years: Legião Urbana (1985), Dois (Two) (1986), Que País É Esse? (What country is this?) 1978/1987 (1987), which contains individual and/or collective songs composed by Renato Russo, in the period of Aborto Elétrico band (1978-1982) and his single Trovador Solitário (Lonely Troubadour) (1982). This research is based on theoretical and methodological framework of Discourse Analysis, as like in Pêcheux s studies (1990, 1997, 2009) and brazilian researches like Orlandi (1997, 2004, 2005, 2007, 2008, 2012); Mariani (2003, 2008); Nunes (2006) Rodriguez-Alcalá (2011), which enabled to check the discursive functioning present in said of linguistic materiality in the songs, like the unsaid, that is on the perspective of founding silence, possibility of saying and silence local, silencing, of the censorship in the period in question; and others discursive materialities, as the nonverbal corresponds to the sonority. So that the frequently references about the thought and the life story of Renato Russo, the bandleader happens because the existing literature about the band and your beginning have him like the main interlocutor. The stories about Renato and his band are blending into. So, the 32 songs were subdivided into three albums in five thematic units, presenting the youth interrelationships subject built on three levels: individual, social and institutional. Finally, we note that first constitued youth was corresponding to young upper-middle class, located in a space that allowed many gaps, even between repression of the dictatorship, and, allies with own comprehend that had and still remains, the that these subjects are still in formation, whatever the FD, allowing to have speeches with divergent positions of existing, without it really meant a break up with these. On the other hand, when this condition is comprehend, the subjects appropriated of the repetition of the imposed conditions, to paraphrase his own life, doing of the same something different